High-resolution NMR techniques in organic chemistry - Claridge, Timothy D. W. (Elsevier, 2016)
High-Resolution NMR Techniques in Organic Chemistry, Third Edition describes the most important NMR spectroscopy techniques for the structure elucidation of organic molecules and the investigation of their behaviour in solution. Appropriate for advanced undergraduate and graduate students, research chemists and NMR facility managers, this thorough revision covers practical aspects of NMR techniques and instrumentation, data collection, and spectrum interpretation. It describes all major classes of one- and two-dimensional NMR experiments including homonuclear and heteronuclear correlations, the nuclear Overhauser effect, diffusion measurements, and techniques for studying protein-ligand interactions. A trusted authority on this critical expertise, High-Resolution NMR Techniques in Organic Chemistry, Third Edition is an essential resource for every chemist and NMR spectroscopist.